NMR characterization of a tight sand's pore structures and fluid mobility: An experimental investigation for CO2 EOR potential. (August 2020) - Dong, Xu; Shen, Luyi W.; Liu, Xuefeng; Zhang, Pengyun; Sun, Yuli; Yan, Weichao; Jiang, Liming; Wang, Fei; Sun, Jianmeng
Abstract: Successful designs of the enhanced oil recovery operation and production forecasts require careful characterization of the reservoir rocks' pore structures and fluids within. In contrary to the commonly adopted assumptions, strengths of the bonding forces resisting fluid displacement in tight sands do not necessarily correlate with the pore sizes. Free fluid (FF) exists across pores of a broad spectrum of sizes and vice versa; fluids bonded firmly to the pore surface by capillary force (i.e., capillary bound fluid, CAF) and electrochemical forces (i.e., clay bound fluid, CBF) may exist in larger pores too; this brings the need of laboratory experiments, particularly at an environment similar to that in-situ. Here, we investigate the pore size distribution and fluid movement in tight sand samples. Fluids in the fully saturated samples are removed sequentially via centrifugation and thermal treatment. NMR responses measured during this process allows the establishment of the characteristic T 2 curves of T FF, T CAF, and T CBF . We compare these curves with the T 2 curves measured during cycles of a laboratory-scale CO2 HnP (huff-n-puff) experiments to assess the recovery rate against fluid types and pore sizes. Low field NMR experiments allow us to investigate the fluid displacements across pores of different sizes, represented by the T 2 relaxation times, at pressurized environments. Through these experiments, we found most FF, including those stored in medium/small-sized pores, are recovered within the first two cycles along with significant CAF from small to medium pores; no displacement of CBF is observed. Highlights: Novel NMR experiments determine the hydrocarbon recovery of different types of fluids across pores of various sizes. Analysis based solely on pore sizes can produce misleading results of reserve estimates and production forecasts. Recoverable free fluid may exit in small pores; non-recoverable clay/capillary bound fluid may exist in large pores.